European dimensions of sustainable development - National University of Food Technologies (My University, 2024)
Proceedings of the VI International Conference on European Dimensions of Sustainable Development present abstracts of the reports of the Conference held on May 15 – 17, 2024 at the National University of Food Technologies, Kyiv, Ukraine (online) under the support of Erasmus+ projects #101085243-ProEU-ERASMUS-JMO-2022-HEI-TCHRSCH and #101127449-EcoEurope-ERASMUS-JMO-2023-HEI-TCH-RSCH. The proceedings cover economic, environmental and social aspects of sustainable development of European sustainability; advanced technologies for the sustainable development; russian invasion of Ukraine as the threat of European sustainability; as well as European Studies on sustainable development. Funded by the European Union. Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Education and Culture Executive Agency (EACEA). Neither the European Union nor EACEA can be held responsible for them.

У збірнику матеріалів VI Міжнародної конференції «Європейські виміри сталого розвитку» представлені тези доповідей конференції, що відбулася 15 - 17 травня 2024 року в Національному університеті харчових технологій, м. Київ, Україна (онлайн) за підтримки проектів Еразмус+ #101085243-ProEU-ERASMUS-JMO-2022-HEI-TCHRSCH та #101127449-EcoEurope-ERASMUS-JMO-2023-HEI-TCH-RSCH. Матеріали охоплюють економічні, екологічні та соціальні аспекти сталого розвитку європейської сталості; передові технології для сталого розвитку; російське вторгнення в Україну як загроза європейській сталості; а також європейські дослідження з питань сталого розвитку. Фінансується Європейським Союзом. Погляди та думки, висловлені в публікації, належать виключно автору(ам) і не обов'язково відображають позицію Європейського Союзу або Європейського агентства з питань освіти і культури (ЕАСЕА). Ані Європейський Союз, ані EACEA не несуть за них відповідальності.